Konsep Ilmu dan Pembelajarannya Mengikut Pandangan Abu Al-Barakat al-Baghdadi (547H) - Wan Abdullah, Wan Suhaimi (Jurnal Usuluddin, 1998)
The epistemology is one of the most important fields in philosophy. In the history of Islamic Philosophy, this field had been studied within the metaphysics, especially those earlier philosophers. The latest Islamic philosopher like Abu al-Barakat al-Baghdadi, Fakhr al-Din al-Razi and Nasir al-Din al-Tusi had made the special attention of it where they studies it more profoundly and separately. However, the connection between this fields is still exist. This article tries to perform a part of Abu al-Barakat theory of knowledge and its relation to the metaphysics.